Generous Geometries: An organismic/existential exploration of giving (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Using many sources and voices, from writers and data from my research and reflecting on aspects of clinical work, particularly in relation to areas of love and sexuality – marriage, affairs, consensual non-monogamy – I will present the case for generosity. An open movement of becoming, intimately listening and opening towards the ambiguous stirring evoked within oneself in encounters with others.
Keywords: Generosity; consensual non-monogamy; existential therapy; sexuality; desire